Repercussões da pandemia de Covid-19 na saúde mental materna e no vínculo de mães com crianças nascidas no cenário de distanciamento físico em contextos de vulnerabilidade social - Silva, Jordan Prazeres Freitas da (2023)
Introduction: The COVID-19 pandemic has had a negative impact on the mental health of part of the population, especially those considered to be at risk. Objective: To understand the repercussions of the COVID-19 pandemic on maternal mental health and on the bond of mothers with children born in a scenario of physical distancing in contexts of social vulnerability in Fortaleza, Ceará. Method: This is a field study with a qualitative approach and of an exploratory nature. It took place between May and July 2023, used semi-structured interviews to collect data and used Bardin's Thematic Content Analysis as a lens to process the empirical material. It was submitted to the Research Ethics Committee (CEP) of the Federal University of Ceará (UFC) for consideration of the ethical propositions of the research and obtained opinion number. 5.159,476. Results: Eighteen (18) women who had children during the period of physical distancing, established by State Decree No. 33,519, of March 19, 2020, of the State of Ceará, were interviewed. After processing the content apprehended in the work, three structuring axes were elaborated based on the characteristics of Thematic Content Analysis, which helped categorize the results found: Maternal mental health in adverse contexts related to the COVID-19 pandemic, Lifestyles and social relations of women who experience scenarios of social vulnerability and Constitution of motherhood and the bond between the mother-baby binomial. Initially, it became clear how some of the participants endured various situations of psychological suffering in their contexts, and how they developed strategies to cope with adverse experiences. In addition, it was found that several of the women interviewed did not have a formal paid job, that they all did some kind of household chore, and that this, coupled with the habit of waking up early, led to extreme tiredness, little time for rest and few leisure activities. In addition, some of the women had strong social and emotional support networks (mainly made up of family, friends, religious institutions and health services), while others had weakened these. Furthermore, most of the participants had unplanned pregnancies, some of which were even unwanted. In addition, we learned that the social imposition of incorporating the desire for pregnancy was also present in the participants' lives. It was also identified that for some mothers, the initial experiences of the baby's birth were relevant to the mother-baby bond, while for others, this attachment occurred through daily exchanges with the child (during care, breastfeeding and play). Finally, it was understood that there is weakness in public policies aimed at maternal mental health, as well as a lack of knowledge about access to RAPS devices, and that even in the context of the COVID-19 pandemic, and the reality caused by it, mental health care continues, in some scenarios, with poor access. Final considerations: From the perspective of ethical-political care, it is necessary to expand the scientific framework of the central theme of the thesis, and it is hoped that the results can serve as a pillar, including for state discussions in the planning of intersectoral public policies for the maternal and child public.